Produção de carne de cordeiros da raça ideal e cruzas ideal x border leicester terminados em campo natural suplementado e pastagem cultivada com ou sem suplementação - Almeida, Henrique Silla Lopes de (2004)
The objectives of this work were to verify the feeding systems and genotype effect on Polwarth and Polwarth x Border Leicester crossbred lambs performance and carcass characteristics. The experiment was carried out in two times: on the first, before slaughter, were estimated the pasture and animal characteristics; and the second, after slaughter, were estimated the biometric measurements and carcass characteristics. Forty eight not castrated ram lambs weaned at the 60 days of age were used, being: 16 of Polwarth pure breed, 16 1/2 Border Leicester x 1/2 Polwarth and 16 3/4 Border Leicester x 1/2 Polwarth crossbred lambs. Animals of each genetic group were into three feed systems: cultivated pasture + supplementation, cultivated pasture and natural pasture + supplementation; where they stay until get 65% of their genetic group adult weight. The supplement was commercial with 18,1% CP t the 1,5% BW/day level. The experimental design was complete randomized using a 3x3 factorial design. The crossbreeding with the Border Leicester breed leave Polwarth ewes to produce lambs with better average daily weight gains, and lambs of half blood Border Leicester x Polwarth dams are heavier at the weaning than the lambs of Polwarth dams. In relation to the pasture, the use of ryegrass, red clover and birdfoot trefoil together at the cultived pasture in forage offer levels around 9,5% and the forage mass of 840kg/ha did not limited the weight gain of the lambs. On this experiment conditions, the supplementation use do not higher stocking rate at the cultived pasture. In relation the carcass characteristics, the crossbreed lambs gaves better carcass yield, had higher biometrics measure, increase the carcass length, leg depth and ribeye area and lower internal fat, marble and fat depth amount. Based on these results this work leave to conclude as possible to produce meat with Polwarth lambs and to increase the production using the crossbreeding with the Border Leicester.